2D анімація як візуальний ключ до суспільної свідомості - Дейнеко, Ж. В.; Ярміш, А. І. (ТОВ «Видавництво Ліра-К», 2025)
The work explores 2D animation as a tool of visual communication capable of capturing audience attention and conveying complex, socially significant topics in an accessible and emotionally engaging form. The focus is placed on its ability to evoke empathy, increase viewer engagement, and enhance information retention. An example of animation use to raise awareness about HIV/AIDS is presented.
Keywords: анімація; 2D animation